Late Modern Characteristics in The Handmaid’s Tale - Jiménez-Esclusa, Héctor (2022)
This article proposes a study of The Handmaid’s Tale (Margaret Atwood, 1985) within late modernity by examining three characteristics: theocracy, patriarchy, and internal dialogue. To fulfill the objective of the article, the novel will be contrasted with the two characteristics that Zygmunt Bauman attributes to this late modernity in which, although there has been a change with respect to the first modernity, there is no break but a continuation. The first characteristic consists in the loss of the telos of the political community. The other characteristic that Bauman adheres to late modernity is a change in the political perspective in which it is renounced that it is society as a whole that attempts a social change and the self-assertion of the individual is privileged. This work is justified because a good part of the previous works that also study this novel are prior to the appearance of the self-denominated Islamic State and the push of populist movements in the West; and they also predate the Me Too movement. This novel allows us to adapt the categories of analysis to a different historical moment from the one that signed several of the novels of the dystopian canon.